PENGEMBANGAN MEDIA ANIMASI POWTOON BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN PPKn MATERI MUSYAWARAH DI KELAS IV SD - Rika Eliza Matondang; Nila Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is a conscious and systematic effort to prepare students to face future challenges, especially in the rapidly evolving era of globalization. Based on interviews in Grade IV at SD Negeri 101879 Kanan 2, Desa Buntu Bedimbar, several issues were identified during the Civics Education (PPKn) lessons. One problem was the teacher's infrequent use of media in the learning process. The use of educational media, especially audiovisual tools like animation applications such as Powtoon, Canva, and Articulate Storyline 3, was not yet optimal. This led to student boredom and disengagement during lessons. In response to this issue, the researcher sought to develop Powtoon Animation Media based on Problem-Based Learning (PBL) for Civics Education lessons focused on deliberation material in Grade IV elementary school. The objective of this research was to evaluate student responses, the validity, practicality, and effectiveness of the developed media in increasing student engagement during Civics Education lessons on deliberation material. The research employed a Research and Development (R&D) approach using the ADDIE development model. Overall, the results of the media validation received a score of 90%, and the material validation scored 83%, both indicating that the media was highly feasible and valid. The teacher's response to the developed media scored 85%, indicating it was highly suitable and valid. The student response achieved a score of 82%, also indicating high feasibility. Additionally, the student engagement questionnaire showed a score of 81%, categorized as excellent. Based on these results, the Powtoon Animation Media based on Problem-Based Learning to enhance student engagement in Civics Education lessons on deliberation material in Grade IV elementary school is considered highly feasible and valid.